A theory of entrepreneurial overconfidence, effort, and firm outcomes - Craig R. Everett; Richard J. Fairchild (The Journal of Entrepreneurial Finance (JEF), 2015)
We present a theory of entrepreneurial behavior that explores the relationship between overconfidence and successful firm outcomes, such as acquisition or IPO. In our model, increasing overconfidence produces two conflicting effects on the probability of a successful outcome: it not only induces an entrepreneur to increase the riskiness of a venture (which lowers the likelihood of successful exit), but also drives higher entrepreneurial effort, increasing likelihood of a successful exit. Due to this conflict, a kinked or U-shaped relationship may exist between overconfidence and positive outcomes. Furthermore, our model suggests that increased outside equity mitigates the effects of overconfidence.
Keywords: G32; G34; L26; M13; 650; Overconfidence; Entrepreneurship; Cognitive Bias; IPO; Mergers & Acquisitions